2006
DOI: 10.1124/jpet.105.097667
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of ΔF508-CFTR (Cystic Fibrosis Transmembrane Conductance Regulator) by Curcumin: Involvement of the Keratin 18 Network

Abstract: The most common mutation in the cystic fibrosis transmembrane conductance regulator (CFTR) gene, ⌬F508, causes retention of ⌬F508-CFTR in the endoplasmic reticulum and leads to the absence of CFTR Cl Ϫ channels in the plasma membrane. ⌬F508-CFTR retains some ClϪ channel activity so increased expression of ⌬F508-CFTR in the plasma membrane can restore Cl Ϫ secretion deficiency. Recently, curcumin was shown to rescue ⌬F508-CFTR localization and function. In our previous work, the keratin 18 (K18) network was imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 36 publications
0
48
0
Order By: Relevance
“…In this regard, an extensive effort has been devoted to the development of a CF "interaction" network through data-mining efforts provided by GeneGo (CF MetaMiner [CF]) (Wright et al 2009) that provides a carefully annotated, systems level view of components contributing to CFTR function and correction of disease etiology. Moreover, in addition to studies on the WT and DF508-CFTR interactome (Wang et al 2006), a series of bioinformatic studies have analyzed both the genomic and whole cell proteomic responses of human tissue to disease (Lipecka et al 2006;Ollero et al 2006;Pollard et al 2006;Singh et al 2006;Singh et al 2008). Together, these studies illuminate an extensive network of interactions that will need to be restored to obtain full correction of the disease phenotype (Fig.…”
Section: Characterization Of New Targets Affecting Restoration Of Tismentioning
confidence: 99%
“…In this regard, an extensive effort has been devoted to the development of a CF "interaction" network through data-mining efforts provided by GeneGo (CF MetaMiner [CF]) (Wright et al 2009) that provides a carefully annotated, systems level view of components contributing to CFTR function and correction of disease etiology. Moreover, in addition to studies on the WT and DF508-CFTR interactome (Wang et al 2006), a series of bioinformatic studies have analyzed both the genomic and whole cell proteomic responses of human tissue to disease (Lipecka et al 2006;Ollero et al 2006;Pollard et al 2006;Singh et al 2006;Singh et al 2008). Together, these studies illuminate an extensive network of interactions that will need to be restored to obtain full correction of the disease phenotype (Fig.…”
Section: Characterization Of New Targets Affecting Restoration Of Tismentioning
confidence: 99%
“…These investigators have suggested that blockade of this chaperone interaction by the use of SERCA inhibitors allows misfolded DF508 CFTR to escape the ER, reach the cell surface, and function as a Cl 2 channel (3). These findings precipitated a remarkable number of investigations and resulted in several papers, indicating that SERCA pump inhibitors like curcumin and/or thapsigargin can (4)(5)(6)(7)(8)(9) or cannot (10-13) enhance DF508 CFTR trafficking to the plasma membrane and apical epithelial chloride transport.…”
mentioning
confidence: 99%
“…Other small molecules, such as curcuminoids (12)(13)(14), 4-phenylbutyrate (4-PBA, buphenyl) (15,16), and CFTRcor-325 (17), are also potential candidates to rescue F508del-CFTR function. Most of these small molecules act after short-term incubation (2-24 hours, depending on studies and laboratories) of CF cells, and little if any information is available concerning their long-term effect.…”
mentioning
confidence: 99%